Feeding High-Fat Diet Accelerates Development of Peripheral and Central Insulin Resistance and Inflammation and Worsens AD-like Pathology in APP/PS1 Mice - Mengr, Anna; Strnadová, Veronika; Strnad, Štěpán; Vrkoslav, Vladimír; Pelantová, Helena; Kuzma, Marek; Comptdaer, Thomas; Železná, Blanka; Kuneš, Jaroslav; Galas, Marie-Christine; Pačesová, Andrea; Maletínská, Lenka (Nutrients, 2023)
Alzheimer's disease (AD) is a progressive brain disorder characterized by extracellular amyloid-β (Aβ) plaques, intracellular neurofibrillary tangles formed by hyperphosphorylated Tau protein and neuroinflammation. Previous research has shown that obesity and type 2 diabetes mellitus, underlined by insulin resistance (IR), are risk factors for neurodegenerative disorders. In this study, obesity-induced peripheral and central IR and inflammation were studied in relation to AD-like pathology in the brains and periphery of APP/PS1 mice, a model of Aβ pathology, fed a high-fat diet (HFD). APP/PS1 mice and their wild-type controls fed either a standard diet or HFD were characterized at the ages of 3, 6 and 10 months by metabolic parameters related to obesity via mass spectroscopy, nuclear magnetic resonance, immunoblotting and immunohistochemistry to quantify how obesity affected AD pathology. The HFD induced substantial peripheral IR leading to central IR. APP/PS1-fed HFD mice had more pronounced IR, glucose intolerance and liver steatosis than their WT controls. The HFD worsened Aβ pathology in the hippocampi of APP/PS1 mice and significantly supported both peripheral and central inflammation. This study reveals a deleterious effect of obesity-related mild peripheral inflammation and prediabetes on the development of Aβ and Tau pathology and neuroinflammation in APP/PS1 mice.
Keywords: Insulin Resistance; inzulinová rezistence; obesity; Inflammation; amyloid-β; Alzheimer’s disease; tau protein; Alzheimerova nemoc; Alzheimer Disease; glucose intolerance; Diet, High-Fat; Diabetes Mellitus, Type 2; dieta s vysokým obsahem tuků; amyloidní beta-protein; neurozánětlivé nemoci; diabetes mellitus 2. typu; insulin resistance; zánět; Animals; Neuroinflammatory Diseases; Amyloid beta-Peptides; zvířata; neuroinflammation; inflammation; myši; APP/PS1; Mice